Body sway and performance at competition in male pistol and rifle Olympic shooters - Mon Daniel; Zakynthinaki Maria; Cordente Carlos; Barriopedro Maria; Sampedro Javier (Sciendo, 2014)
Study aim: We examine the body sway differences between a) pistol and rifle and b) elite and national level senior male Olympic shooters, as well as the possible relation between body sway and performance at competition in Olympic shooting.